COMPUTATIONAL ANALYSIS OF AERODYNAMIC PARAMETERS FOR SUPERSONIC ARTILLERY PROJECTILES - RAHMAN, MD RAFIQUR (IJRDO - Journal of Mechanical And Civil Engineering, 2020)
Aerodynamic parameters have a huge impact on the trajectory of a projectile which in turn results in its range and accuracy. The influence aerodynamic parameters for the estimation of trajectory elements are drag Coefficients, lift Coefficients, angles of attack, muzzle velocity, atmospheric conditions, and the projectile shape and size. Thus proper methods for determining the drag and lift forces of the projectile is very important. The trajectory of a projectile through the air is affected both by gravity and by aerodynamic forces. In this paper 57 mm and 37 mm anti aircraft projectile was considered for the analysis. Here main emphasis was given to determine pressure coefficient, Drag coefficients, lift coefficient of the projectiles at different angle of attack. To study the aerodynamic parameters the experiment was conducted in an open circuit subsonic wind tunnel where uniform flow velocity is maintained across the flow direction. For the experiment varied angles of the attack was considered. Here inclined manometer was used to find out the surface static pressure and the pressure coefficient was determined from that. Then the drag & lift forces and their coefficients was determined. Finally, for the computational analysis, the ANSYS Software was used to simulate the experimental data.